Pola Bagi Hasil Usaha Garam Rakyat di Kabupaten Pamekasan, Jawa Timur - Campina Illa Prihantini; Yusman Syaukat; Anna Fariyanti (Jurnal Agribisnis Indonesia, 2016)
Sharecropping system is wellknown as a disincentive agricultural system (Marshall 1920). It has been a culture that is very difficult to be deleted in rural area. Almost 70,5% of salt production business in Pamekasan regency applied this system, although it does not give more adventages to the sharecroppers. This study aimed to analyze the sharecropping system in salt production by estimating the profit taken by landlords and sharecroppers. Beside that, this study aimed to identify the factors affecting sharecropper’s decission by using binery logistic regression. The results showed that the landlords and the sharecroppers have a significant difference in the mean of their profit. This result is significant for α=5%. Sharecropper’s decission is affected significantly by the last education of sharecropper, number of sharecropper’s family, and cost of fund. This study recommended the government, landlords, sharecroppers, middleman, and the stakeholder to cooparate and make a forum that can give a better welfare to the sharecroppers.